2015
DOI: 10.4103/0189-6725.172538
|View full text |Cite
|
Sign up to set email alerts
|

Complications of hypospadias surgery: Experience in a tertiary hospital of a developing country

Abstract: Background:Over 300 different operations have been described for the management of hypospadias. In recent times, the numbers of operations used in various centres have gradually reduced as the principles necessary to ensure adequate cosmetic and functional results with minimum complications are better understood. The aim of this article was to review the different types of operations used for managing hypospadias in a tertiary hospital in a developing country, to analyse the complications of surgery and discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
2
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 32 publications
(47 reference statements)
0
9
2
4
Order By: Relevance
“…Mammo, et al (2018) showed 34.3% complication rate in their 128 patients of distal hypospadias repair in Ethiopia [5]. A report from Ghana (2020) showed 28% complication rate for TIP repair and another report from Nigeria (2017) showed 33.1% fistula rate [3,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammo, et al (2018) showed 34.3% complication rate in their 128 patients of distal hypospadias repair in Ethiopia [5]. A report from Ghana (2020) showed 28% complication rate for TIP repair and another report from Nigeria (2017) showed 33.1% fistula rate [3,18].…”
Section: Discussionmentioning
confidence: 99%
“…Tubularized incised plate (TIP) urethroplasty has become an attractive method worldwide for hypospadias repair since its introduction in 1994 for distal hypospadias and 1998 for mid shaft and proximal hypospadias [1]. Although reports from developed world show excellent outcome of this procedure, the descriptions from many developing countries still show more fistula rates and other complications [2][3][4][5][6]. Moreover, there is still debate about the ultimate outcome of incising a urethral plate and the application of TIP where the urethral plate is narrow.…”
Section: Introductionmentioning
confidence: 99%
“…The most common urological conditions observed at the GNCPS were hypospadias (70 cases per year) and cryptorchidism (126 cases per year). Hypospadias cases are sometimes referred after a failed correction by inexperienced adult surgeons [12]. Inguinal hernia/hydrocele (210 cases/year) was the second most frequent discharge diagnosis after appendicectomy (237 cases/year).…”
Section: Hospital Management and Clinical Governancementioning
confidence: 99%
“…"Santo Spirito", Pescara, Italy. 12 Fondazione "Mangiagalli", Milan, Italy. 13 Clinica Pediatrica, Università "Gabriele d'Annunzio", Chieti-Pescara, Italy.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…The results of surgery for hypospadias patients are often unsatisfactory, with reported rates of complications reaching 40% and even more (Appeadu-Mensah et al, 2015;Mammo et al, 2018). For distal hypospadias, the highest complication reported reaching 33% (Klijn, Dik, & de Jong, 2001;Stein, 2012).…”
Section: Consideration Of Complicationsmentioning
confidence: 99%